2021
DOI: 10.1021/acs.analchem.1c02371
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Ion Fluxes in Nanopipettes: Detection and Analysis of Electro-osmosis of the Second Kind

Abstract: Nanopipettes are finding increasing use as nano "test tubes", with reactions triggered through application of an electrochemical potential between electrodes in the nanopipette and a bathing solution (bath). Key to this application is an understanding of how the applied potential induces mixing of the reagents from the nanopipette and the bath. Here, we demonstrate a laser scanning confocal microscope (LSCM) approach to tracking the ingress of dye into a nanopipette (20−50 nm diameter end opening). We examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The simulated results indicated that the concentration distribution of 2MeIm was unaffected by the electric field. In contrast, the concentration of Zn 2+ dramatically increased with the potential magnitude under negative potentials, with the distribution concentrated at the tip orifice. Therefore, when a negative potential was applied, the ZIF-8 nanoparticles were likely to grow inside the nanopipet within a confine space, which was likely to be condensed into clusters. On the contrary, as the distribution of Zn 2+ was mainly outside the nanopipette under positive potentials; it could be deduced that the ZIF-8 nanoparticles were formed at the tip place and then driven outside the nanopipette by the electric field; thus, the ZIF-8 particles could be delivered into the bulk solution outside the nanopipette.…”
Section: Resultsmentioning
confidence: 99%
“…The simulated results indicated that the concentration distribution of 2MeIm was unaffected by the electric field. In contrast, the concentration of Zn 2+ dramatically increased with the potential magnitude under negative potentials, with the distribution concentrated at the tip orifice. Therefore, when a negative potential was applied, the ZIF-8 nanoparticles were likely to grow inside the nanopipet within a confine space, which was likely to be condensed into clusters. On the contrary, as the distribution of Zn 2+ was mainly outside the nanopipette under positive potentials; it could be deduced that the ZIF-8 nanoparticles were formed at the tip place and then driven outside the nanopipette by the electric field; thus, the ZIF-8 particles could be delivered into the bulk solution outside the nanopipette.…”
Section: Resultsmentioning
confidence: 99%
“…c 0 was the primary concentration of the dyes flowing from the nanopipette to the cytoplasm edge. Navier–Stokes equations were used to describe the electro-osmotic flow of the fluorescence molecules as shown in the Supporting Information. …”
Section: Methodsmentioning
confidence: 99%
“…The asymmetric ion transport under diluted electrolyte solution gives rise to the ion current rectification (ICR) effect. , This effect has be further developed into a nanopore sensing approach where the characteristic current–voltage curves can be modulated by the changes on the surface of the nanopore induced by the presence of analytes (Figure B) . Furthermore, recent studies on the time-dependent dynamics of mass transport into nanopipettes and characterization of nanopipette transport physics will benefit a wide range of nanoscale experimentation, including the synthesis of inorganic and organic materials and the stabilization of unusual polymorphs by confinement …”
Section: High-throughput Nanoporesmentioning
confidence: 99%